Role of ICT in Teaching and Learning Integrated Science in Primary Schools in Central Division Kabale Municipality. - Tumukurate, Dickson (Kabale University, 2024)
The Role of ICT in Teaching and Learning Integrated Science in Primary Schools in Central Division Kabale Municipality. Primary schools in Central Division Kabale Municipality District. A case study of Kabale Rutooma Primary School Kabale District. It aimed at examining the effect of teaching and learning on students' discipline in Primary schools of Kabale Municipality, establishing the effect of teaching and learning on student performance in Primary schools of Kabale Municipality, and examining the challenges hindering teaching and learning teaching in schools of Kabale Municipality. The study was conducted through cross-sectional survey design alongside qualitative and qualitative paradigms. A cross-sectional research design was used to generate the information by explaining to the individual respondents the gist of the study. A Cross-sectional research design was used to establish the importance of teaching and learning in Primary schools. The cross-sectional research design was used because it is able to generate a sizable amount of data from a cross-section of the target population. The target population included teachers head teachers and students from the selected Primary school that is Rutooma primary, Kabale District. The sample size consisted of 20 teachers, 02 district education officers, 02 inspectors of schools, 02 head teachers, and 216 students. The determination of sample size is based on guidelines given by Morgan and Krejcie (1970). Qualitative data was descriptively analyzed by examining the content of the data by identifying the distinctive categories that emerged from the data. Quantitative data accruing from the study was analyzed using descriptive statistics. The study findings on the effect of teaching and learning on students' discipline showed that teaching and learning have shaped the values of the students as reported by 15%, enhanced the sense of responsibility 16%, improved respect for authority by 17%, has led to community engagement 14%, it has improved cohesion among students 14%, it has also motivated students through national pride 08% and 17% reported that teaching and learning has improved behavioral change. From the study results, the researcher concluded that the study suggests a multifaceted relationship between teaching and learning and academic performance among students. Teaching and learning appear to enhance social cohesion, motivation, cultural identity, civic responsibility, engagement, and critical thinking skills—all factors contributing positively to academic achievement. It was recommended that there was a need for regular workshops focusing on patriotic education that can equip teachers with innovative teaching methods and resources and ensure that future educators receive comprehensive training in civic education, including teaching and learning, which will prepare them better for their roles.